Functional Exhaustion of Type I and II Interferons Production in Severe COVID-19 Patients - Ruetsch, Caroline; Brglez, Vesna; Crémoni, Marion; Zorzi, Kévin; Fernandez, Céline; Boyer-Suavet, Sonia; Benzaken, Sylvia; Demonchy, Elisa; Risso, Karine; Courjon, Johan; Cua, Eric; Ichai, Carole; et al. (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has emerged in Wuhan in December 2019 and has since spread across the world. Even though the majority of patients remain completely asymptomatic, some develop severe systemic complications. In this prospective study we compared the immunological profile of 101 COVID-19 patients with either mild, moderate or severe form of the disease according to the WHO classification, as well as of 50 healthy subjects, in order to identify functional immune factors independently associated with severe forms of COVID-19. Plasma cytokine levels, and cytokine levels upon in vitro non-specific stimulation of innate and adaptive immune cells, were measured at several time points during the course of the disease. While inflammatory cytokines: IL1β, IL6, IL8 and TNFα were significantly increased in moderate and severe COVID-19 patients (p<0.0001 for all cytokines), reduced levels of both type I and type II interferons upon in vitro stimulation were correlated with increased disease severity (IFNα: p>0.0001 mild vs moderate and severe; IFNγ: p=0.0002 mild vs moderate and p<0.0001 mild vs severe) suggesting a functional exhaustion of interferons production. This lower production of IFN remained significant even when corrected for monocytes and lymphocyte count. Patients with a level of IFNγ upon in vitro stimulation lower than 15 IU/mL at admission and before specific treatment were more likely to develop complications during hospitalization (p=0.0002) confirmed also by multivariable analysis (p=0.0349 OR=0.98 [0.962; 0.999]). During follow-up, non-stimulated plasma IL6 levels decreased between the moment of admission to the hospital and at the last observation carried forward for patients with favorable outcome (p=0.02148). In vitro, treatment with type I interferon restores type II interferon secretion in COVID-19 patients while pro-inflammatory cytokines secretion: IL6, IL1β remains stable or decrease respectively. These results a) demonstrate a functional exhaustion of both innate and adaptive immune response in severe forms of COVID-19; b) identify interferons I and II as new potential biomarkers of severity; and c) highlight the importance of targeting interferons when considering COVID-19 treatment in order to re-establish a normal balance between inflammatory and Th1 effector cytokines.